Analisis Pengaruh Kualitas Pelayanan dan Citra Merk Terhadap Loyalitas Konsumen dengan Kepuasan Pelanggan Sebagai Variabel Mediasi (Studi Pada Toko Roti Papa Cookies Seluruh Area Jawa Timur) - Aprista Restuningtika; Muryati Muryati; Survival Survival (Universitas Batanghari Jambi, 2023)
MSMEs in Indonesia are already too dominant in terms of numbers and even tend to always increase causing a problem, especially in terms of increasingly fierce business competition. For business actors who are just starting out, they must strengthen their research and knowledge of the market before starting a business. Likewise, for SMEs who were originally established, business actors must think more creatively to survive. One of the efforts that can be done by SMEs is by paying attention to consumer loyalty. The purpose of this study was to determine whether the quality of service and brand image can affect consumer loyalty to the UMKM Bakery Papa Cookies. This study uses quantitative methods with Partial Least Square (PLS) analysis to examine the relationship between variables. The sample taken amounted to 96 consumers. The results of this research show that the better the quality of service and brand image can increase customer satisfaction, so that it has an impact on increasing consumer loyalty at Papa Cookies Bakery.